A Novel Sequential Activation Method for the Locomotion of Quadrupedal Soft Robots - Sampaio, Rafaela; Silva, Fabrício; Carvalho, Cristiano; Haddad, Diego; Araujo, Gabriel; França, Felipe (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2019: Anais do VII Simpósio Brasileiro de Robótica e XVI Simpósio Latino Americano de Robótica, 2019)
The absence of a general theory of how to control soft structures is the biggest challenge in soft robotics. In this work the application of Scheduling by Multiple Edge Reversal (SMER) as an artificial Central Pattern Generator (CPG) is proposed for the activation of soft quadrupedal robots. In order to evaluate the proposed application, a soft device was developed for the purpose of being tested as a robot's paw, and SMER technique was applied in order to create a logic controller for this device. Image processing techniques were used to evaluate the functionality of the proposed strategy, with help of an experimental apparatus consisting on infrared markers, an infrared light, and a camera. Test results showed that it is completely possible to use SMER techniques to activate soft robotics systems; also the test revealed that the techniques employed to develop and test the device were appropriate and limited resources were needed.